"Litoral": Pontevedra’s weekly journal and the autonomy in Galician’s Literary field - Acuña, Ana (Madrygal. Revista de Estudios Gallegos, 2012)
This article pretends to give value to Pontevedra periodic publication Litoral. On one side we try to show how this weekly journal exemplified in its pages the fight for the autonomy in Galician’s literary filed, and on the other side we reproduce the interviews the Journal gave to Valentin Paz Andrade and to Celso Emilio Ferreiro.